Diallel analysis in cassava adapted to the midaltitude valleys environment - Jaramillo, Gustavo; Morante, N; Pérez Velásquez, Juan Carlos; Calle, F.; Ceballos, H.; Arias, B.; Bellotti, Anthony C. (Wiley, 2005)
Cassava (Manihot esculenta Crantz) is an important commodity for industrial processes in tropical countries as one of the few alternatives to compete with imported maize (Zea mays L.). To maintain this competitiveness, cassava breeding needs to be as efficient as possible. This study provides one of the first attempts to produce quantitative genetic data to aid breeding efficiency, through the analysis of a diallel set among nine parental clones adapted to the midaltitude valleys environment. Thirty clones represented each F1 cross (with three exceptions). Evaluations were conducted in two contrasting environments with three replications in each location. The specific combining ability (SCA) effects were relatively more important than general combining ability (GCA) effects for root yield. In the case of harvest index, dry matter content (DMC) and plant type architecture GCA effects were about twice as large as those from SCA effects. Reaction to mites (Mononychellus tanajoa Bondar) and white flies (Aleurotrachelus socialis Bondar) (based on single-location data) showed the strongest influence of GCA effects on the expression of a given trait. Yield data demonstrates the excellent potential of this crop for the tropical production of starch and source of energy in animal feed that could compete with the international markets.